Financial narratives in crisis - Emily Rosamond (Finance and Society, 2020)
Amin Samman's History in Financial Times addresses the need to develop more nuanced ways to account for history, given that succession, as a model of making history, so clearly falls short. His emphasis on narrative throughout the book is hugely important at a moment of widespread narrative dysfunctionality in which the distinction between fact and fiction comes to be widely contested.
Keywords: 300